2013
DOI: 10.1107/s1744309113028170
|View full text |Cite
|
Sign up to set email alerts
|

The tertiary structure of an i-type lysozyme isolated from the common orient clam (Meretrix lusoria)

Abstract: To evaluate the structure-function relationships of invertebrate lysozymes, a new invertebrate-type (i-type) lysozyme was isolated from the common orient clam (Meretrix lusoria) and the tertiary structure of this enzyme was determined. Comparison of the tertiary structure of this enzyme with those of chicken and Venerupi philippinarum lysozymes revealed that the location of the side chain of the second catalytic residue, an aspartic acid, and the N-acetylglucosamine trimer bound at subsites A-C were different.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The structure of the bacterial produced mutanolysin is quite distinct from C-type lysozymes like hen egg white lysozyme [ 72 , 73 ]. In contrast G-type and I-type lysozymes produced by eukaryotes are structurally similar to C-type lysozyme and likely the result of divergent evolution [ 74 , 75 ]. However, at this time it is not known if RsiV can bind to G-type or I-type lysozymes.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the bacterial produced mutanolysin is quite distinct from C-type lysozymes like hen egg white lysozyme [ 72 , 73 ]. In contrast G-type and I-type lysozymes produced by eukaryotes are structurally similar to C-type lysozyme and likely the result of divergent evolution [ 74 , 75 ]. However, at this time it is not known if RsiV can bind to G-type or I-type lysozymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, electron density maps did not reveal the presence of NAG3 molecule, suggesting that the inhibitory effect of sodium ions was at play. Interestingly, both sodium ions and NAG3 were present in the crystallization conditions of TjL (PDB ID: 2DQA 23 ) and MlL lysozyme (PDB ID: 3AB6 33 ). In contrast to our study, these structures contained NAG3 molecules but no sodium ions.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of enzymes is an important index of mollusk physiology and immune status. The invertebrate-type LZM plays an important role in the immunity of invertebrates, including bivalves (Itoh et al 2007 ; Xue et al 2007 ; Kuwano et al 2013 ). Gagnaire et al ( 2006 ) reported that the activity of LZM in the blood cells of the oyster Crassostrea gigas decreased significantly under the stress of exposure to polycyclic aromatic hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%